2022
DOI: 10.3390/ijerph19116651
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Clinical Practicum Assessment Tool for the NAACLS-Accredited Biomedical Science Program

Abstract: Student perspectives on their final year clinical placements in biomedical sciences at Qatar University are assessed using the clinical practicum assessment tool (CPAT), which was developed in-house following accreditation body requirements. The tool, which we call the CPAT-Qatar University (CPAT-QU), covers the three clinical practicum domains: practicum content, preceptors, and competencies. Here, we validate this tool. The CPAT-QU has 27 Likert-scale questions and free-text open questions. CPAT-QU readabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Understanding disease mechanism and possible side effects of the vaccine was shown to be important in other groups in Jordan and other Middle East countries. A study performed in three Middle Eastern countries (Jordan, Saudi Arabia, and Kuwait) found that participants had moderate overall COVID-19 knowledge, and had better knowledge about disease prevention and control [ 27 , 28 ]. Higher education participants had a good level of understanding, which could be linked to their level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding disease mechanism and possible side effects of the vaccine was shown to be important in other groups in Jordan and other Middle East countries. A study performed in three Middle Eastern countries (Jordan, Saudi Arabia, and Kuwait) found that participants had moderate overall COVID-19 knowledge, and had better knowledge about disease prevention and control [ 27 , 28 ]. Higher education participants had a good level of understanding, which could be linked to their level of education.…”
Section: Discussionmentioning
confidence: 99%
“…This study made use of a previously designed and validated tool that was developed at QU. The tool is called Clinical Practicum Assessment Tool at Qatar University (CPAT-QU) and consists of 27 items (Table S2) [11]. The first part of CPAT-QU tool explores the satisfaction level of MLS graduates in terms of clinical-practicum organization, content, evaluation criteria and length.…”
Section: Research Instrumentmentioning
confidence: 99%
“…It mandates the completion of the clinical practicum in the last semester of a four-year curriculum before the award of a Bachelor of Science degree in MLS. The main objective of this study was to survey MLS graduates at Qatar University using a previously developed and validated tool, called CPAT-QU, in order to gather descriptive data on students' perceptions of the clinical practicum content, teachers and entry-level competencies required to enter their profession [11]. The study examined graduates' perspectives on content, teachers and clinical training and their satisfaction rate based on the skills they gained during their training.…”
Section: Introductionmentioning
confidence: 99%